A Comparative Discussion on the Selection of Cardiac Hypertrophy Models: TAC Surgery Vs Ang II Infusion [Letter] - Yang H; Wang X (Dove Medical Press, 2024)
Huiye Yang, Xiaotao Wang Department of Hematology, The Affiliated Hospital of Guilin Medical University, Guilin, People’s Republic of ChinaCorrespondence: Huiye Yang; Xiaotao Wang, Department of Hematology, The Affiliated Hospital of Guilin Medical University, Guilin, People’s Republic of China, Email huiyeyang1@163.com; wxw99321@163.com